2021
DOI: 10.2217/cer-2020-0185
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of video laryngoscopy by a major academic anesthesia department

Abstract: Aim: To describe the adoption patterns of intubating devices used at a major teaching and research facility. Materials & methods: Retrospective analysis of 2012–2019 data on frequency and trends in airway management devices collected from our anesthesia information management system. Results: Use of direct laryngoscopy was more frequent, but there was a downward trend in use over time (p < 0.008) in favor of video laryngoscopy (VL), which increased significantly (p < 0.008). The largest growth among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While the long-touted obsolescence of DL has not yet occurred, there has been a steady erosion in market share versus VL. The authors have demonstrated this in a large, tertiary care academic facility [9]; it also occurs in the community hospital. VL and use of the bougie are recommended as the initial back-up when intubation proves problematic in recent landmark publications [10,11].…”
mentioning
confidence: 85%
“…While the long-touted obsolescence of DL has not yet occurred, there has been a steady erosion in market share versus VL. The authors have demonstrated this in a large, tertiary care academic facility [9]; it also occurs in the community hospital. VL and use of the bougie are recommended as the initial back-up when intubation proves problematic in recent landmark publications [10,11].…”
mentioning
confidence: 85%